Protection of Children's Rights: A Review of Child Marriage Policies in Indonesia, Malaysia, and India - Kusmayanti, Hazar; Judiasih, Sonny Dewi; Yuanitasari, Deviana; Rajamanicham, Ramalinggam (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Child marriage is a phenomenon that continues and develops, the low knowledge and understanding of the community towards the perception of marriage. Child marriage should not be allowed anywhere in the world as it is a practice that violates general human rights and discriminates against women. Purposes of the Research: In this research, the author will compare the prevention of child marriage in Indonesia, Malaysia, and India.Methods of Research: This research uses a normative juridical approach method. Researchers will study and examine the factors that cause child marriage and its legal protection to prevent child protection in Indonesia, Malaysia, and India. This research uses descriptive analytical research specifications by determining the laws and regulations relating to legal theories that are the object of research.Results of the Research: Indonesia increased the minimum marriage age for both sexes from 18 to 19 with the enactment of Law No. 16 of 2019. Malaysia, meanwhile, sets a maximum marriage age of eighteen. Initiatives to reduce the legal age of marriage, especially for women, have been made in both nations for socio-political and socio-cultural reasons. Alongside these initiatives, India has also ratified several conventions designed to end child marriage. These include the 1976 International Covenant on Civil and Political Rights (ICCPR) and the 1976 International Covenant on Economic, Social, and Cultural Rights (ICESCR), as well as the 1956 Supplementary Convention on the Abolition of Slavery, the Slave Trade, and Institutions and Practices Similar to Slavery.